Type-4 Phosphodiesterase (PDE4) Blockade Reduces NETosis in Cystic Fibrosis - Totani, Licia; Amore, Concetta; Piccoli, Antonio; Dell’Elba, Giuseppe; Di Santo, Angelo; Plebani, Roberto; Pecce, Romina; Martelli, Nicola; Rossi, Alice; Ranucci, Serena; De Fino, Ida; Moretti, Paolo; et al. (Frontiers in Pharmacology, 2021)
Neutrophilic inflammation is a key determinant of cystic fibrosis (CF) lung disease. Neutrophil-derived free DNA, released in form of extracellular trap (NETs), significantly correlates with impaired lung function in patients with CF, underlying their pathogenetic role in CF lung disease. Thus, specific approaches to control NETosis of neutrophils migrated into the lungs may be clinically relevant in CF. We investigated the efficacy of phosphodiesterase (PDE) type-4 inhibitors, in vitro, on NETs release by neutrophils from healthy volunteers and individuals with CF, and in vivo, on NETs accumulation and lung inflammation in mice infected with Pseudomonas aeruginosa. PDE4 blockade curbed endotoxin-induced NETs production and preserved cellular integrity and apoptosis in neutrophils, from healthy subjects and patients with CF, challenged with endotoxin, in vitro. The pharmacological effects of PDE4 inhibitors were significantly more evident on CF neutrophils. In a mouse model of Pseudomonas aeruginosa chronic infection, aerosol treatment with roflumilast, a selective PDE4 inhibitor, gave a significant reduction in free-DNA in BALF. This was accompanied by reduced citrullination of Histone H3 in neutrophils migrated into the airways. Roflumilast-treated mice showed a significant improvement in weight recovery. Our study provides the first evidence that PDE4 blockade controls NETosis in vitro and in vivo, in CF relevant models. Since selective PDE4 inhibitors have been recently approved for the treatment of COPD and psoriasis, our present results encourage clinical trials to test the efficacy of this class of drugs in CF.